Perceptions of the Malaysian general public on community pharmacy-based weight management services - Rohit Kumar Verma; Thomas Paraidathathu; Nur Akmar Taha; Wei Wen Chong (Taylor & Francis Group, 2018)
Background Obesity is now widely regarded as a main contributor to poor health. Involvement of community pharmacists can be a valuable tool in obesity management. However, there is still a lack of data in Malaysia on the potential involvement of and opportunities for community pharmacists in providing weight management services. Thus, it is essential to investigate the perceptions of the general public on weight management services in the community pharmacy setting. To evaluate the general public's perceptions on weight management services by community pharmacists in terms of perceived availability, utilization and factors influencing acceptability of services. Methods A descriptive, cross sectional-survey was conducted using a self-administered questionnaire comprising of sections that focused on public preferences and options on weight management approaches, perceived availability of extended services and resources provided by community pharmacists in relation to weight management, utilization of these services and resources, and factors influencing acceptability of weight management services provided by community pharmacists. The questionnaires were distributed to the general public aged 18 years and above in Klang Valley, Malaysia. Results A total of 730 respondents with a median age of 31 years participated in this study. Majority of respondents ranked dieticians as their preferred first line of consultation, with only about a quarter of respondents ranking community pharmacists as their preferred first or second line of consultation. Although more than half show of the study respondents perceived that community pharmacies they had visited offered services for measuring weight, height, blood pressure, blood glucose and blood cholesterol, fewer perceived that community pharmacies provided advice on physical activity and healthy eating to achieve weight loss. Additionally, majority of the respondents indicated that they had not utilized these services. However, most respondents perceived that community pharmacists should provide weight management services. The main factors influencing acceptability show of services included training of pharmacists, payment, waiting time and the issue of privacy. Conclusion The findings of this study demonstrated that the majority of respondents were in support of weight management services in community pharmacy; however only a low percentage reported utilizing these services. Factors influencing acceptability of services included payment, waiting time and the issue of privacy. With adequate training among pharmacists and increased awareness of services among the public, community pharmacists could play a larger and important role in addressing the issue of obesity in Malaysia.